Safety and Efficacy Triple Drug Therapy (IDA) versus Two-drug therapy DA in Lymphatic Filariasis: A Systematic Review - Ita octafia; Riza Mazidu Sholihin (Yayasan Ahmad Mansyur Nasirah, 2025)
Lymphatic filariasis (elephantiasis) is a parasitic disease caused by Wuchereria bancrofti, Brugia malayi, and Brugia timori, and is transmitted through the bite of infected mosquitoes. This disease is classified as a neglected tropical disease and has been targeted for global elimination through mass drug administration strategies. This systematic review aimed to evaluate the safety and effectiveness of a single-dose triple-drug therapy consisting of ivermectin, diethylcarbamazine, and albendazole (IDA) compared with the two-drug regimen of diethylcarbamazine and albendazole (DA) based on randomized clinical trials. A literature search was conducted in PubMed using the keyword “elephantiasis,” yielding eleven relevant studies published within the last five years. The results indicated that moderate adverse events occurred more frequently with IDA therapy, although most were mild in nature, while serious adverse events were more commonly reported with DA therapy. No significant differences were observed in filarial antigen levels between the groups. IDA therapy was well tolerated and considered as safe as DA, while demonstrating greater effectiveness in clearing microfilariae. With high coverage of mass drug administration, widespread use of IDA has the potential to accelerate the elimination of lymphatic filariasis.